Gary Cooper American hero - Meyers, Jeffrey 1939- (Morrow, 1998)
A study of "the laconic star," from his youth in England to his film career and "tempestuous relationships" with a number of famous actresses to "his controversial involvement with the House Un-American Activities Committee and the Hollywood blacklist."--Jacket.